(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
John Keats’ poetic concept of oneness helps to forge a literary framework, which enables Julio Cortázar to re-make several characters and unusual circumstances in his narrative works. The Argentinean writer traces the main theoretical concepts in the works and letters of this English poet in order to give an innovative turn to his incipient way of conceiving short stories from the very beginning, those posthumously published in the collection called La otra orilla. Then, Cortázar’s dense and lengthy Imagen de John Keats is the unanswerable proof of his outstanding acquisition of this Romantic poetics, essentially as an instrument to reach his literary ambitious goal: the rise among the new ones in Latin American prestigious writer listings.